Biogas Production from Food Waste Using Nanocatalyst. (31st July 2022) - Bharathi, P.; Dayana, R.; Rangaraju, Magesh; Varsha, V.; Subathra, M.; Gayathri,; Sundramurthy, Venkatesa Prabhu
Abstract : The food waste management has become a very important part in the modern world. In the olden days, the population was very low, so that the low waste produced was easily disposed by dumping it under the soil. However, nowadays, due to high population, amount of waste is produced high which could not be dumped due to the land pollution. To overcome this problem, the food waste must be managed or utilized properly to give zero waste. Therefore, this work focused on the production of biogas from food waste through the anaerobic digestion process using iron oxide nanoparticles. The iron oxide nanocatalyst from red mud reduced the process time for the anaerobic digestion was by 5.38% compared to the noncatalytic process. The produced biogas analysis done through GCMS analysis and calculated by comparing the both anaerobic degradation setup with and without nanocatalyst. Nanocatalyzed degradation contains 50% high amount of methane and 23.5% of total amount of biogas when compared to nonnanocatalyzed degradation.